Meningkatan Kemampuan Motorik Kasar Anak Melalui Permainan Tradisional Kucing Dan Tikus - Halimatus Zahroh; Kartini Marzuki; Susilawati Susilawati (Universitas Negeri Makassar, 2022)
Based on the results of observations that have been made by researchers in group A of Tunas Harapan kindergarten Kertagena Look. There are several problems related to hard motoric skills that are still not optimal because children are not free to explore, and hard motoric skills are still limited, as in gymnastics movements and static learning methods. Therefore, efforts are being made to optimize children's hard motoric skills through traditional cat and mouse games. This research is the type of classroom action research with the form of research used is qualitative and quantitative. The study can be called successful because five children are in the Very Good Development criteria (80%), three children are in the 68.25% percentage included in the Developing As Expected criteria, and two children are in the 50% percentage entering the Starting to Develop standards. The average rate of hard motoric skills of children in Group A of Tunas Harapan Kindergarten is said to be successful because the researchers set indicators of success in the assessment criteria for Developing According to Expectations (70%). Based on the results of the research carried out, it can be concluded that the use of traditional cat and mouse games can improve the hard motoric skills of group A of Tunas Harapan kindergarten Kertagena Look.